RETRACTED: Interaction between zinc and selenium bio-fortification and toxic metals (loid) accumulation in food crops - Bayanati, Mina; Al-Tawaha, Abdel Rahman; Al-Taey, Duraid; Al-Ghzawi, Abdul Latief; Abu-Zaitoon, Yousef M.; Shawaqfeh, Samar; Al-Zoubi, Omar; Al-Ramamneh, Ezz Al-Dein; Alomari, Laith; Al-Tawaha, Abdel Razzaq; Dey, Abhijit (Frontiers in Plant Science, 2022)
Biofortification is the supply of micronutrients required for humans and livestock by various methods in the field, which include both farming and breeding methods and are referred to as short-term and long-term solutions, respectively. The presence of essential and non-essential elements in the atmosphere, soil, and water in large quantities can cause serious problems for living organisms. Knowledge about plant interactions with toxic metals such as cadmium (Cd), mercury (Hg), nickel (Ni), and lead (Pb), is not only important for a healthy environment, but also for reducing the risks of metals entering the food chain. Biofortification of zinc (Zn) and selenium (Se) is very significant in reducing the effects of toxic metals, especially on major food chain products such as wheat and rice. The findings show that Zn- biofortification by transgenic technique has reduced the accumulation of Cd in shoots and grains of rice, and also increased Se levels lead to the formation of insoluble complexes with Hg and Cd. We have highlighted the role of Se and Zn in the reaction to toxic metals and the importance of modifying their levels in improving dietary micronutrients. In addition, cultivar selection is an essential step that should be considered not only to maintain but also to improve the efficiency of Zn and Se use, which should be considered more climate, soil type, organic matter content, and inherent soil fertility. In addition, in this article, the role of medicinal plants accumulating heavy metals is mentioned, and the mechanisms of these plants can be taken into consideration in the direction of bio-enrichment improvement programs.